A reappraisal of the structure of xylosmin. (February 2021) - Prangé, Thierry; Lavaud, Catherine; Massiot, Georges
Highlights: Structure of xylosmin has been corrected. Glucose is D in xylosmin. Configurations in the cyclohexenone and xylosmic acid are: 1S, 2S, 6S. Graphical abstract: Abstract: The structure of xylosmin, a phenol glycoside from Salicaceae has been precised through a new interpretation of previously published X-ray crystallography data. This was based on the assignment of β-d -glucose for the sugar part of the molecule.